Human Periodontal Stem Cells Release Specialized Proresolving Mediators and Carry Immunomodulatory and Prohealing Properties Regulated by Lipoxins. (25th November 2015) - Cianci, Eleonora; Recchiuti, Antonio; Trubiani, Oriana; Diomede, Francesca; Marchisio, Marco; Miscia, Sebastiano; Colas, Romain A.; Dalli, Jesmond; Serhan, Charles N.; Romano, Mario
Abstract: : Unresolved inflammation and tissue destruction are underlying mechanisms of periodontitis, which is linked to dysregulated polymorphonuclear neutrophil (PMN) functions. Lipoxin A4 (LXA4 ) is a specialized proresolving lipid mediator (SPM) that dampens excessive inflammation, promotes resolution, and protects from leukocyte-mediated tissue damage. Human periodontal ligament stem cells (hPDLSCs) represent key players during tissue regeneration and may contribute to resolution of inflammation; thus, they may represent a promising tool in regenerative dentistry. In the present study, we investigated the actions of hPDLSCs on PMN apoptosis and antimicrobial functions, and determined the impact of LXA4 on hPDLSCs. hPDLSCs significantly reduced apoptosis and stimulated microbicidal activity of human PMNs, via both cell-cell interactions and paracrine mechanisms. Lipid mediator metabololipidomics analysis demonstrated that hPDLSCs biosynthesize SPMs, including resolvin D1, D2, D5, and D6; protectin D1; maresins; and LXB4 ; as well as prostaglandins D2, E2, and F2α . LXA4 significantly enhanced proliferation, migration, and wound healing capacity of hPDLSCs through the activation of its cognate receptor ALX/FPR2, expressed on hPDLSCs. Together, these results demonstrate that hPDLSCs modulate PMN functions, and provide the first evidence that stem cells generate SPM and that the LXA4 -ALX/FPR2 axis regulates regenerative functions of hPDLSCs by a novel receptor-mediated mechanism. Significance: These findings uncovered unappreciated features of stem cells from the periodontal ligament, supporting the notion that these cells may act as master regulators of pathophysiological events through the release of mediators that promote the resolution of inflammation and bacterial killing. The study also demonstrated that it is possible to modulate important functions of periodontal stem cells using lipoxin A4, a potent endogenous stop signal of inflammation. Thus, this study revealed an unappreciated anti-inflammatory proregenerative circuit that may be exploited to combat periodontal pathologies using resident stem cells. Moreover, the data may represent a more general template to explain the immunomodulatory functions of stem cells. Abstract : The actions of human periodontal ligament stem cells (hPDLSCs) on polymorphonuclear neutrophil (PMN) apoptosis and antimicrobial functions, and the impact of lipoxin A4 (LXA4 ) on hPDLSCs were investigated. hPDLSCs significantly reduced apoptosis and stimulated microbicidal activity of human PMNs, via both cell-cell interactions and paracrine mechanisms. hPDLSCs also were found to biosynthesize proresolving lipid mediators and prostaglandins. This study also demonstrated that the LXA4 -ALX/FPR2 axis regulates regenerative functions of hPDLSCs by a novel receptor-mediated mechanism.